2018
DOI: 10.1177/1042258718806627
|View full text |Cite
|
Sign up to set email alerts
|

Are Founder-Led Firms Less Susceptible to Managerial Myopia?

Abstract: Considerable evidence suggests that CEOs often behave myopically. It is open to debate, however, whether managerial myopia is equally prevalent among founder-led firms. Drawing on agency theory and stewardship theory, we analyze whether founder-led firms are less likely than nonfounder-led firms to cut R&D expenditures in order to meet the short-term earnings goals suggested by these firms’ past performance histories. Our analysis of Standard & Poor’s 1,500 companies from 1992 to 2013 indicates that my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 136 publications
5
33
2
1
Order By: Relevance
“…Lee et al (2017), for example, found an “overconfidence bias” in founder CEOs (compared with professional CEOs) as displayed in their communication (Twitter use), issuance of high earnings forecasts, and use of stock options. Further, Schuster et al (2018) showed that founder CEOs are less likely to exhibit managerial myopia as measured in R&D cuts. In all, although these studies paint a picture of founders as aggressive, overconfident decision makers, the findings of other studies do not support this view.…”
Section: Founder‐ceo Research Themesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al (2017), for example, found an “overconfidence bias” in founder CEOs (compared with professional CEOs) as displayed in their communication (Twitter use), issuance of high earnings forecasts, and use of stock options. Further, Schuster et al (2018) showed that founder CEOs are less likely to exhibit managerial myopia as measured in R&D cuts. In all, although these studies paint a picture of founders as aggressive, overconfident decision makers, the findings of other studies do not support this view.…”
Section: Founder‐ceo Research Themesmentioning
confidence: 99%
“…Risk-taking Early (nascent) and late (post-IPO) stages Fahlenbrach (2009) Lee et al 2017Overconfidence Abebe and Tangpong (2018) Innovativeness Schuster et al (2018) Abbreviations: CEO, chief executive officer; IPO, initial public offering.…”
Section: Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research and development (R&D) is usually associated with large-scale companies, more emphasis needs to be placed on these activities in SMEs to surpass their competitors (Forsman and Annala, 2012). Schuster et al (2018) report that founder-led firms are less likely than non-founder-led firms to cut R&D expenditures to meet short-term earnings goals.…”
Section: Individual and Firm-level Factorsmentioning
confidence: 99%
“…The level of depression in our dataset followed a right-skewed distribution with many posts having no or little depression. To make inferences about the degree of depression in the data, we performed a log transformation to correct for skewness (Frederiksen, Wennberg, & Balachandran, 2016;Schuster, Nicolai, & Covin, 2018). Posts with depression greater than zero were used in this transformation (Draper & Cox, 1969) and observations without depression were not retained.…”
Section: Methodsmentioning
confidence: 99%